You do not have to succeed, just do not fail: When do soccer coaches get fired?. (16th October 2017) - Elaad, Guy; Jelnov, Artyom; Kantor, Jeffrey
Abstract : This article deals with circumstances leading to the dismissal of a soccer coach. The article is based on results from the Premier League in England over 12 consecutive years. In this paper, we converted the scores of matches (win, draw, and loss) into an index based upon how results were perceived by club owners—those empowered with the decision as to whether or not to fire the coach. The index is based on the difference between the actual and expected results reflected by betting odds. We conclude that to ensure job preservation, the manager does not have to succeed—he just must not fail.